Effect of plasticizer on PMMA grafted natural rubber polymer electrolyte / Siti Nakhirah Sharip Huddin - Sharip Huddin, Siti Nakhirah (2013)
In this research, poly(methyl methacrylate) (PMMA), 30% PMMA grafted natural rubber (MG30), Ammonium Triflate NH4CF3SO3 and propylene carbonate (PC) were used in the preparation of solid polymer electrolyte (SPE) and gel polymer electrolyte (GPE). Gel polymer electrolytes containing MG30- NH4CF3SO3 + PC will be prepared by solution cast technique. The composition between polymer and salt will be investigated using Fouriertransformed infrared spectroscopy. The ionic conductivity of the electrolytes will be determined by the ac impedance spectroscopy studies. The other admittance behaviour will be analyzed based on the impedance spectroscopy data obtained.